LINC00261 Suppresses Cisplatin Resistance of Esophageal Squamous Cell Carcinoma Through miR-545-3p/MT1M Axis - Wang, Lijun; Wang, Xiaojun; Yan, Pengwei; Liu, Yatian; Jiang, Xuesong (Frontiers in Cell and Developmental Biology, 2021)
Accumulating evidence has suggested that long noncoding RNAs (lncRNAs) regulate the progression of esophageal squamous cell carcinoma (ESCC) by various pathophysiological pathways. Here, our study explored the possible function of the lncRNA LINC00261 (LINC00261) on cisplatin (DDP) resistance of ESCC and its relative molecular mechanisms. In the study, we found that LINC00261 was downregulated in ESCC tissues, cell lines, and DDP-resistant ESCC patients. Besides, overexpression of LINC00261 not only inhibited cell proliferation, and DDP resistance but also promotes cell apoptosis. Further mechanistic research showed that LINC00261 sponged miR‑545-3p which was negatively correlated with the expression of LINC00261. In addition, functional experiments revealed that upregulation of miR-766-5p promoted proliferation and enhanced DDP resistance. Subsequently, MT1M was testified to be the downstream target gene of miR-545-3p. Rescue experiments revealed that overexpression of MT1M largely restores miR-545-3p mimics-mediated function on ESCC progression. In conclusion, LINC00261 suppressed the DDP resistance of ESCC through miR-545-3p/MT1M axis.